Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4103/ijo.ijo_2682_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the results of anophthalmic prostheses

Abstract: Purpose: Anophthalmic sockets cause disfigurement that may result in emotional and social distress. The choice of procedure and implant is based upon the surgeon’s experience. There remains no standardization of cosmetic result. We sought to identify quantifiable anatomical features and functional properties related to a successful cosmetic result in patients with ocular prosthesis and to determine correlations between self-reported and third-party assessment of cosmetic success. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A primary orbital implant is recommended to achieve an optimal result 25 . Vardizer et al 12 reported that the cosmetic result of anophthalmic patients wearing a prosthesis, as evaluated by professional examiners, is good in most patients (Figure 2) and that a good result was related to the ability of the prosthetic eye to move in comparison to the contralateral eye, to eyelid symmetry, and socket fullness.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…A primary orbital implant is recommended to achieve an optimal result 25 . Vardizer et al 12 reported that the cosmetic result of anophthalmic patients wearing a prosthesis, as evaluated by professional examiners, is good in most patients (Figure 2) and that a good result was related to the ability of the prosthetic eye to move in comparison to the contralateral eye, to eyelid symmetry, and socket fullness.…”
Section: Managementmentioning
confidence: 99%
“…Ocular or prosthesis motility is an important factor contributing to normal facial appearance. 12 Unfortunately, the motility of the artificial eye is usually reduced compared with the motility of the contralateral eye, especially in the extreme directions of gaze. A primary orbital implant is recommended to achieve an optimal result.…”
Section: Prosthesis Motilitymentioning
confidence: 99%
See 1 more Smart Citation